Logistics in the Falklands War a case study in expeditionary warfare - Privratsky, Kenneth L. author (2014)
First in-depth study of the ingenious logistics plan for the Falklands War. Draws valuable lessons for military planners today and in the future. Written by highly experienced and senior military logistician.